Diplomasi Maritim “Rempah” di Nusantara: Perjalanan dari Maluku Sampai ke Pelabuhan Malaka - Berkat Immanuel Salempa; Seniwati Seniwati (Journal of Creative Student Research, 2024)
Spice commodities are very important commodities in trade in the past, spice trading routes built by the people of the archipelago and traders from India and China, caused many local ports to emerge which developed rapidly into ports that were visited by many merchant ships from various regions, past ports such as Maluku, Banda, Makassar, and Malacca. In the context of global trade, a trade network was formed that connected the western world as consumers and the eastern world as producers of commodities. The regions in the archipelago are known as centers of spice production that are very diverse, almost every region of the archipelago has typical spices that are traded. This study aims to look at the history of the spice route in the archipelago and its benefits as a form of diplomacy in ancient times, which can make the economy in various regions of the archipelago develop well, the spread of religion and cultural exchange can occur due to diplomacy through the spice route. With this aim, this study uses a library research method related to archaeological data and historical source searches. The results of this study obtained information that the most sought-after spices in the past were cloves, nutmeg, and mace, which could be found in the Maluku and Banda regions. From the existence of these three spices, a spice route was created starting from Maluku to the port of Malacca, which at that time was the largest gathering point for Chinese, Indian, and European traders.